Power system security and voltage collapse: a line outage based indicator for prediction - Moghavvemi, M.; Faruque, M.O. (Elsevier, 1999)
With the increased loading and exploitation of the power transmission system, the problem of voltage stability and voltage collapse is attracting more and more attention. Continuous monitoring of the system status is therefore a necessary requirement. This article is concerned with power system security and investigates a proposed voltage collapse proximity indicator. For each line of the system, a line stability index is calculated based on the power flow through that line. The value of the line stability index is then used for predicting contingency outage of the lines and hence study the voltage collapse of the system. The described technique does not involve computational complexities and therefore can be easily implemented. The performance of the proposed indicator was tested on the IEEE 24 bus Reliability Test System and was found to be accurate and computationally feasible.